Comparação da acurácia de dois tomógrafos na detecção de fraturas radiculares em dentes tratados endodonticamente - Knecht, Milena Filippini (2024)
One of the main reasons for the extraction of endodontically treated teeth is the occurrence of vertical root fractures (VRF), and their diagnosis is still a challenge in the dentist's routine. Periapical radiography is, in general, the complementary exam of first choice for detecting RVF, however, several factors, such as angulation and contrast, can interfere with the image. Three-dimensional techniques, such as tomography, are more reliable as they are capable of eliminating distortions and overlaps. However, they also present some limitations due to the formation of artifacts, when the RVF to be diagnosed is close to hyperdense material, in addition to requiring a minimum thickness of the fracture so that it can be noticed. Therefore, this study was proposed to compare the accuracy of two CT scanners in detecting root fractures in endodontically treated teeth. The tomographic images were acquired on the OP300® tomography machine (Instrumentarium) and the X800® tomography machine (J Morita). The sample consisted of 42 extracted teeth, single-rooted with a single canal, without cracks/fractures and accentuated curvatures. The root canals were prepared by the same operator using the Reciproc reciprocating file system, up to R40 or R50 (Reciproc - VDW®) or using manual instrumentation, depending on the caliber of the initial instrument, irrigated abundantly and filled. The tomographic images were interpreted by two endodontic specialists. Statistical analysis was performed using Jamovi software. The OP300® tomography scanner (Instrumentarium) showed better sensitivity and specificity results compared to the X800® tomography scanner (J Morita). The chi-square test indicated greater accuracy for the OP300® tomograph. There was reasonable agreement between examiners for both the OP300® tomography scanner (Instrumentarium) and the X800® tomography scanner (J Morita). The results of this study indicated a considerable occurrence of error in the detection of RVF for both tomographs used, in addition to reasonable agreement between the examiners for both tomographs.